Pseudomonas luteola Bacteremia in Newly Diagnosed Systemic Lupus Erythematosus - Mazin Barry (Case Reports in Infectious Diseases)
Pseudomonas luteola is rarely considered as a human pathogen.There are only fewer than twenty reported cases of P. luteola infections since 1950. It has been described in both immunocompromised and immunocompetent patients as a cause of both nosocomial and community-acquired infections. We report a rare case of P. luteola infection in a previously healthy patient who was admitted to hospital with a first presentation of Systemic Lupus Erythematosus (SLE) presenting with P. luteola bacteremia.